2018
DOI: 10.1021/acssuschemeng.7b04118
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reforming of Biomass Derived Crude Glycerol in Water: A Sustainable Approach for Improved Hydrogen Generation Using Ni(OH)2 Decorated TiO2 Nanotubes under Solar Light Irradiation

Abstract: Crude glycerol (10% w/w) is produced as a substantial byproduct during the industrial production of biodiesel via transesterification processes. Catalytic hydrogen (H 2 ) generation by utilizing crude glycerol and solar light is considered as a promising avenue. The present work illustrates enhanced rates of H 2 generation and cocatalyst behavior of Ni(OH) 2 decorated on TiO 2 nanotubes dispersed in aqueous crude glycerol solution (industrial byproduct) under solar light irradiation. The catalyst characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…The results show that the enhanced photocatalytic activity originated from the introduction of Ni(OH) 2 nanoparticles, which unfolds a co‐catalytic property. In addition, Reddy and co‐workers 90 found that crude glycerol could be reformed to generate hydrogen by TiO 2 nanotubes modified with Ni(OH) 2 QDs under solar light irradiation, as presented in Figure 4A. It is interesting that the high electronegativity of Ni(OH) 2 material could intensify the shuttling of photoexcitons, so as to enhance the photocatalytic hydrogen production performance.…”
Section: Progress Of Ni‐based Cocatalysts For Hydrogen Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the enhanced photocatalytic activity originated from the introduction of Ni(OH) 2 nanoparticles, which unfolds a co‐catalytic property. In addition, Reddy and co‐workers 90 found that crude glycerol could be reformed to generate hydrogen by TiO 2 nanotubes modified with Ni(OH) 2 QDs under solar light irradiation, as presented in Figure 4A. It is interesting that the high electronegativity of Ni(OH) 2 material could intensify the shuttling of photoexcitons, so as to enhance the photocatalytic hydrogen production performance.…”
Section: Progress Of Ni‐based Cocatalysts For Hydrogen Evolutionmentioning
confidence: 99%
“…(A) Plausible reaction mechanism for H 2 generation on Ni(OH) 2 /TNT from crude glycerol 90 . (B) Schematic illustration of the photoinduced fabrication of Pt/Ni(OH) 2 ‐C 3 N 4 86 [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Progress Of Ni‐based Cocatalysts For Hydrogen Evolutionmentioning
confidence: 99%
“…Modified wet impregnation route was adapted to disperse the NiO co-catalyst nanoparticles on CuS photocatalyst [29]. Typically, 0.5 g of Polyvinylpyrrolidone ((C6H9NO)n average mol.…”
Section: Cus-nio Nanocompositementioning
confidence: 99%
“…The experimental process followed for photocatalytic hydrogen evolution and processing parameters used in gas chromatography for accurate quantification of hydrogen gas was followed as in our recent publication [29]. The pristine CuS, NiO and composite CuS/NiO (CPN-1, CPN-2 and CPN-3) were firstly tested in photocatalytic water splitting experiments under nature Sunlight irradiation.…”
Section: Experimental Procedures For Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…[16] The hole in the TiO 2 valence band has a highly positive potential of + 2.95 V versus NHE. Moreover, because photocatalytic H 2 production is part of the overall sustainability research, the utilization of biomass-derived alcohols (e. g., methanol, [17] ethanol, [18] glycerol, [19] and formaldehyde [20] ) as sacrificial (electron) donors has recently become an attractive green route for H 2 production. [18] The overall catalytic H 2 evolution is a complex process that is under ongoing research.…”
Section: Introductionmentioning
confidence: 99%